New Strategies for Treatment of Inflammatory Bowel Disease - Nielsen, Ole Haagen (Frontiers in Medicine, 2014)
The etiology of inflammatory bowel disease (IBD), of which ulcerative colitis (UC) and Crohn’s disease (CD) are the two most prevailing entities, is unknown. However, IBD is characterized by an imbalanced synthesis of pro-inflammatory mediators of the inflamed intestine, and for more than a decade tumour necrosis factor- (TNF) α has been a major target for monoclonal antibody therapy. However, TNF inhibitors are not useful for one third of all patients (i.e. “primary failures”), and further one third lose effect over time (“secondary failures”). Therefore other strategies have in later years been developed including monoclonal antibodies targeting the interleukin (IL)-6 family of receptors (the p40 subunit of IL-12/IL-23) as well as monoclonal antibodies inhibiting adhesion molecules (the 47 heterodimers), which direct leukocytes to the intestinal mucosa. Recently small molecules, which are inhibitors of Janus kinases (JAKs), hold promise with a tolerable safety profile and efficacy in UC, and the field of nanomedicine is emerging with siRNAs loaded into polyactide nanoparticles that may silence gene transcripts at sites of intestinal inflammation. Thus, drug development for IBD holds great promise, and patients as well as their treating physicians can be hopeful for the future.